As práticas de planejamento das ações de controle da tuberculose: a discursividade dos sujeitos gestores - Barrêto, Anne Jaquelyne Roque (2014)
Currently, Tuberculosis remains as a big public health problem. It is a challenge to the professionals working in this area and the society in general way too. An essential tool to manage it is the health planning, it grows the development at work and clarifies goals and commitments shared by organizations. The non-participation and lack of knowledge by professionals revels a little political commitment within the actions to control the disease. This study had as a goal to analyze the speech made by the professionals involved in health area linked to the practice in the actions to control tuberculosis. The approach used was qualitative, done in João Pessoa city, Paraiba state, Brazil. We considered it as priority to control tuberculosis. The subjects that took part of it were 25 professionals from the Health area that actuated in the gesture or gesture teams in the city. To analyze the empirical material we used the technical- analytical material to the speech analyze from French matrix. The professionals arguments displayed the absence of planning in the services of basic attention in relation to the actions used to control tuberculosis, thus the number of cases are reduced and its detection is still done in a passive way. In those services where they did a planning to control tuberculosis, their speech stressed a practice of planning with strong centralized, hierarchical and fragmented way. Another aspect identified is the practice of planning turned to campaign actions with speeches during some days. In this way, the organization of the health service follows the biomedical model. In the ideological field, the speeches of the professionals are linked to the practice of planning based in the hegemonic rationality management. Than it suggests the implementation of management and pedagogue processes which support the theoretical and reflexive thoughts on the planning of actions to control tuberculosis, in special a strategic planning considering this one as strong base to the Brazilian sanitary reform.